(untitled) (ResearchJet Journal of Analysis and Inventions, 2022)
The fourth generation (4G) mobile communication network has been introduced in almost all countries. However, with the development of wireless mobile systems and the increase in the types of services, some problems arise in technologies that cannot support 4G. Today, technologists all over the world have started implementing 5G to meet the expectations of users. Index modulation is seen as a promising modulation in 5G. In this work, the characteristics of index modulation used in 5G are considered.